PERBEDAAN SKALA NYERI PADA PEMBERIAN TERAPI SHORTWAVE DIATHERMI DENGAN PENAMBAHAN TERAPI LATIHAN PADA PASIEN CALCANEUS SPURS DI RS. GRANDMED LUBUK PAKAM, TAHUN 2018 - Isidorus Jehaman; Indra Alamsyah (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2019)
The most common cause cited for plantar heel pain is biomechanical abnoemalities that lead to pathologic stress to the plantar soft tissues. Localized nerve entrapment of the medial calcaneal or muscular branch off the lateral plantar nerve may be a contributing factor. Sample of 14 subjects were divided into two groups, each group consist of 7 people. Control Group treated with the addition of exercise therapy. Measuring the degree of pain was used Visual Analogue Scale. This study used an experimental study or quasi experiment with pre test and post test group design. Techniques sampling by Purposive Sampling. Data processing and analysis of data using paired sample t-test. Result: Obtained difference of pain scale shortwave diathermy with the addition of exercise theraphy to patients calcaneus spurs with a mean value after control group of 3.29 treathment with SD amounting to 1.113 and then a mean value after control group of 2.57 with SD 0.535. There is the effect of a significant increase pain scale of shortwave diathermy with the addition of exercise therapy after statistical test result prove that the p value = 0,021 (p <0,05). Conclusion : there is difference of pain scale in the provision shortwave diathermy with the addition of exercise theraphy to patient calcaneus spurs.